ASSESSMENT OF CULINARY CLASS DEMONSTRATION METHODS ON STUDENTS’ PERFORMANCE: VIDEO VERSUS LIVE STREAMING (Journal of Event, Tourism and Hospitality Studies, 2021)
The temporarily close of educational institutions due to the Covid-19 lockout situation affected educators at every level of education to conduct classes online. This study explored whether the use of video demonstration significantly improves students' performance of learning culinary compared with control group counterparts who were exposed to the live streaming demonstration. In addition, students' perceptions of the instructions are assessed. A quasi-experimental study design was used for this study. The study sample consisted of 36 undergraduate Hospitality students enrolled in a culinary course. Sixteen students in the experimental group and 20 students in the control group were exposed to video and live streaming demonstrations, respectively. Both groups were tested about the same target content, ‘Understanding Vegetables and Basic Cuttings’. Students’ performance grades were computed and analyzed to compare students’ learning outcomes between the two groups. Students’ perceptions were assessed based on their opinions of instruction, their self-reported level of understanding of vegetables and basic cuttings, and their level of satisfaction. Results of independent samples t-tests showed; students in the experimental group had a significantly higher performance score and express positive perceptions of the instruction than the students in the control group. The findings from this study would shed light on the instructional strategy suitable for culinary students.